PENGARUH ENVIRONMENTAL INFORMATION DISCLOSURE, KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISIARIS INDEPENDEN, KOMITE AUDIT TERHADAP NILAI PERUSAHAAN - Tanto Eddytia; Hexana Sri Lastanti (STMIK Widuri Jakarta, 2023)
This study aims to determine whether Environmental Information Disclosure, Institutional Ownership, Independent Board of Commissioners, and Audit Committee have an effect on Company Value. The population of this research is all sub-sectors of food and beverage companies listed on the Indonesia Stock Exchange in 2020-2022. The method chosen for sampling was purposive sampling, where sampling was taken based on certain criteria, then 28 food and beverage companies were selected, and multiplied by a period of 3 years so that the amount of data used in this study was 84 samples. The data analysis method used in this study is panel data regression with the Random Effect Model. Data processing in this study used the help of E-Views version 12 software. The results showed that Environmental Information Disclosure (EID), Institutional Ownership (KINS), Independent Board of Commissioners (DKI) had an effect on company value while the Audit Committee (KA) had no effect on the company value.